Pengaruh Pertumbuhan Aset, Struktur Modal, Pengungkapan Enterprise Risk Management Dan Risiko Bisnis Terhadap Nilai Perusahaan (Studi Empiris Pada Perusahaan Sektor Properties Dan Real Estate Yang Terdaftar Di Bursa Efek Indonesia (Bei) Tahun 2019-2023) - Sari, Widya Priska; Dendi Purnama; Syarifudin, Syahrul (Politeknik Raflesia Press, 2025)
The purpose of this study is to provide empirical evidence regarding the effect of asset growth, capital structure, enterprise risk management disclosure and business risk on company value. The objects used in this study are property and real estate sector companies. The sampling technique uses purposive sampling. The sample used was 59 companies or 295 financial report data for 5 periods of 2019-2023. The method used in this study is a descriptive and verification method. The data collection technique uses non-participatory observation techniques while the analysis technique uses panel data regression analysis and uses Eviews 9.0 software. The results of the study, the results of the goodness of fit (f test) show a fit model. And the results of the partial test (T test) show that asset growth, capital structure and enterprise risk management disclosure have a positive and significant effect on company value. While business risk has a negative and insignificant effect on company value. Kata kunci : company value, asset growth, capital structure, enterprise risk management disclosure, and business risk.